Oculomotor-Based Vision Assessment in Mild Traumatic Brain Injury: A Systematic Review. Issue 4 (July 2016) - Hunt, Anne W.; Mah, Katherine; Reed, Nick; Engel, Lisa; Keightley, Michelle
Abstract : Objective: The purpose of this article is to synthesize and appraise the evidence regarding the use of oculomotor-based vision assessment to identify and monitor recovery from mild traumatic brain injury (mTBI). Specific objectives are to (1) identify changes in oculomotor-based vision following mTBI; (2) distinguish methods of assessment; (3) appraise the level and quality of evidence; and, if warranted, (4) determine clinical recommendations for assessment. Methods: A systematic review was undertaken to identify and appraise relevant literature. A search was conducted of 7 databases of peer-reviewed literature from January 1990 to January 2015. Articles were included if study populations were clearly identified as having mTBI and used an assessment of oculomotor-based vision. Articles with pooled data (eg, mTBI and stroke), addressing afferent visual function (eg, visual field deficits) or using single case designs, were excluded. Results: Twenty articles were selected for inclusion. Exploratory findings suggest that measurements of saccades, smooth pursuit, and vergence are useful in detecting changes associated with mTBI. Assessment methods included eye tracker protocols, optometric assessment, and the King-Devick test. Conclusion: The strength of this evidence is not yet sufficient to warrant clinical recommendations. Research using rigorous methods is required to develop reliable, valid, and clinically useful assessment protocols. Abstract : Supplemental Digital Content is Available in the Text.